A Brief Psychological Intervention for Chronic Pain in Primary Care: A Pilot Randomized Controlled Trial. Issue 7 (22nd February 2021) - Miller-Matero, Lisa R; Hecht, Leah M; Miller, Mary Kate; Autio, Kirsti; Pester, Bethany D; Tobin, Erin T; Patel, Shivali; Braciszewski, Jordan M; Maye, Melissa; Ahmedani, Brian K
Abstract: Objective: Although evidence-based psychological interventions improve chronic pain, many patients do not engage in behavioral health services. Offering a brief intervention in a medical setting may provide benefits to patients with chronic pain. The purpose of this study was to examine preliminary outcomes of a brief psychological intervention for chronic pain delivered in primary care. Design: Pilot randomized controlled trial. Setting: Primary care clinic. Subjects: Sixty participants with chronic pain were randomized to a 5-session psychological intervention or treatment-as-usual control group. Methods: Participants completed pre- and post-intervention measures assessing pain severity, pain interference, pain catastrophizing, depression, and anxiety. Results: Most participants (76.7%) randomized to the intervention completed all sessions. Compared to the control group, those in the intervention had decreases in pain severity ( P = .048), pain catastrophizing ( P = .04), and depression ( P = .01) from pre- to post-intervention. Within the intervention group, there was a significant improvement in pain interference scores ( P = 0.02). Within the intervention group, effect sizes were medium to large for changes in pain severity, pain interference, pain catastrophizing, and depression scores. There were no significant changes in anxiety scores. Conclusion: Results suggest that delivery of a brief psychological intervention for chronic pain in primary care appears to offer improvements in pain severity, pain interference, pain catastrophizing, and depression. Findings suggest that shorter-term psychological interventions may offer similar benefits as longer-term ones. Furthermore, offering a brief intervention in primary care may increase access and engagement in behavioral pain management services. Future research should examine this through a fully-powered trial with longer-term outcomes.